2014
DOI: 10.4319/lo.2014.59.5.1715
|View full text |Cite
|
Sign up to set email alerts
|

Surface biological, chemical, and optical properties of the Patagonian Shelf coccolithophore bloom, the brightest waters of the Great Calcite Belt

Abstract: We report surface observations of a mesoscale coccolithophore bloom at the shelf break of the Patagonian Shelf during December 2008, representing the densest coccolithophore population in the Southern Ocean. The bloom was most intense within the Falklands Current, northeast of the Falkland Islands. Emiliania huxleyi dominated bloom waters, with a mixed E. huxleyi and Prorocentrum sp. dinoflagellate bloom to the west and mixed assemblage of diatoms, dinoflagellates, and flagellates to the east. Optical measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
114
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(135 citation statements)
references
References 53 publications
16
114
1
4
Order By: Relevance
“…The total coccolithophore abundances that we observed (up to ∼ 600 cells mL −1 ) agree with previous observations of maximum abundances of between 200 and 500 cells mL −1 in the Atlantic, Pacific, Indian and Australian sectors of the Southern Ocean (Cubillos et al, 2007;Eynaud et al, 1999;Findlay and Giraudeau, 2000;Gravalosa et al, 2008;Mohan et al, 2008;Hinz et al, 2012;Saavedra-Pellitero et al, 2014;Malinverno et al, 2015;Balch et al, 2016). A previous study across Drake Passage (December, 2006), coinciding with the eastern transect (Transect 2), reported similar abundances of up to 600 cells mL −1 (Holligan et al, 2010).…”
Section: Coccolithophore Distribution In the Southern Oceansupporting
confidence: 82%
See 2 more Smart Citations
“…The total coccolithophore abundances that we observed (up to ∼ 600 cells mL −1 ) agree with previous observations of maximum abundances of between 200 and 500 cells mL −1 in the Atlantic, Pacific, Indian and Australian sectors of the Southern Ocean (Cubillos et al, 2007;Eynaud et al, 1999;Findlay and Giraudeau, 2000;Gravalosa et al, 2008;Mohan et al, 2008;Hinz et al, 2012;Saavedra-Pellitero et al, 2014;Malinverno et al, 2015;Balch et al, 2016). A previous study across Drake Passage (December, 2006), coinciding with the eastern transect (Transect 2), reported similar abundances of up to 600 cells mL −1 (Holligan et al, 2010).…”
Section: Coccolithophore Distribution In the Southern Oceansupporting
confidence: 82%
“…nitrate > 10 µmol kg −1 ) and high irradiances (Poulton et al, , 2013Balch et al, 2014). This dominance has now been suggested to result in low integrated calcite concentrations within bloom waters on the Patagonian Shelf (Poulton et al, 2013;Balch et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Southern Ocean coccolithophore populations are dominated by the cosmopolitan species Emiliania huxleyi (Saavedra-Pellitero et al, 2014;Winter et al, 2014) that is thought to be the major component of the "great calcite belt" observed in the vicinity of the Subantarctic Front (SAF) and Polar Front (PF) Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/dsri (Balch et al, 2014). Several studies have reported modern planktic foraminifer abundances and fluxes in the Southern Ocean from net tows (Asioli and Langone, 1997;Mortyn and Charles, 2003;Bergami et al, 2009;Meilland, 2015) and sediment traps (Donner and Wefer, 1994;King and Howard, 2003;Northcote and Neil, 2005;Salter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although neglected for a long time, the presence of coccolithophores in the Southern Ocean has been diagnosed based on an increasing number of direct observations (Winter et al, 2014) and the development of remote sensing methods (Balch et al, 2005(Balch et al, , 2011(Balch et al, , 2014. Southern Ocean coccolithophore populations are dominated by the cosmopolitan species Emiliania huxleyi (Saavedra-Pellitero et al, 2014;Winter et al, 2014) that is thought to be the major component of the "great calcite belt" observed in the vicinity of the Subantarctic Front (SAF) and Polar Front (PF) Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/dsri (Balch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%